Availability and Access to Support Services in a Blended Learning Environment - Amponsah, S.; Ussher, Y.; Amoako, K.B. (My University, 2021)
The transformation in the distance education system has led to the emergence of blended learning approaches that have necessitated effective support to facilitate students learning. This web survey aimed at determining the kinds of support available and accessible to distance education students of the University of Ghana. Data collected from 103 Levels 300 and 400 students and findings from the survey indicated that physical and technological support services were frequently used among the respondents, whereas residential and e-library resources were the least subscribed support services among the students. In terms of social support services, interaction with tutors and interaction with fellow students came up as the main support services available to students while counselling services were absent for these students. It was recommended that the support services that were inadequate, least used, and absent should be provided to enable students to complete their programmes of study successfully.
Research Article
Keywords: Blended Learning; Flipped Classroom; Hybrid; Learning Environment; Sakai Learning Management System; Support Services; Technology